Cardiovascular Safety of Clonidine and Dexmedetomidine in Critically Ill Patients after Cardiac Surgery - Angelina Grest; Judith Kurmann; Markus Müller; Victor Jeger; Bernard Krüger; Donat R. Spahn; Dominique Bettex; Alain Rudiger (Critical Care Research and Practice)
Purpose. The aim of this retrospective study was to assess the haemodynamic adverse effects of clonidine and dexmedetomidine in critically ill patients after cardiac surgery. Methods. 2769 patients were screened during the 30-month study period. Heart rate (HR), mean arterial pressure (MAP), and norepinephrine requirements were assessed 3-hourly during the first 12 hours of the continuous drug infusion. Results are given as median (interquartile range) or numbers (percentages). Results. Patients receiving clonidine (n = 193) were younger (66 (57–73) vs 70 (63–77) years, p=0.003) and had a lower SAPS II (35 (27–48) vs 41 (31–54), p=0.008) compared with patients receiving dexmedetomidine (n = 141). At the start of the drug infusion, HR (90 (75–100) vs 90 (80–105) bpm, p=0.028), MAP (70 (65–80) vs 70 (65–75) mmHg, p=0.093), and norepinephrine (0.05 (0.00–0.11) vs 0.12 (0.03–0.19) mcg/kg/min, p<0.001) were recorded in patients with clonidine and dexmedetomidine. Bradycardia (HR < 60 bpm) developed in 7.8% with clonidine and 5.7% with dexmedetomidine (p=0.51). Between baseline and 12 hours, norepinephrine remained stable in the clonidine group (0.00 (−0.04–0.02) mcg/kg/min) and decreased in the dexmedetomidine group (−0.03 (−0.10–0.02) mcg/kg/min, p=0.007). Conclusions. Dexmedetomidine and the low-cost drug clonidine can both be used safely in selected patients after cardiac surgery.